1993
DOI: 10.1002/hed.2880150108
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoperative frozen section diagnosis in head and neck surgery: Experience at a university medical center

Abstract: We performed 2,210 intraoperative frozen sections on 258 patients from the Otolaryngology-Head and Neck Surgery Service in 1990 and 1991. Surgery involved a wide variety of benign and malignant lesions. Techniques included biopsies for diagnosis, simple excision, thyroid and salivary gland surgeries, lymph node biopsies, composite resections with radical neck dissections, laryngectomies, and skull base surgeries. During the 2-year period, 1,947 (88.1%) sections were requested for evaluation of surgical margins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 10 publications
8
67
0
1
Order By: Relevance
“…9 In this study, these type of errors were observed in 4 margins in 3 patients. Out of which, 0.9 % was false positive and the rest 2.7% were false negative.…”
Section: Table-ii Status Of Surgical Examined Margins On the Basis Ofsupporting
confidence: 46%
“…9 In this study, these type of errors were observed in 4 margins in 3 patients. Out of which, 0.9 % was false positive and the rest 2.7% were false negative.…”
Section: Table-ii Status Of Surgical Examined Margins On the Basis Ofsupporting
confidence: 46%
“…10,11 Error rates for frozen section margins are generally low, with reported frozen-permanent correlation rates as low as 96% and as high as 99%. [10][11][12][13][14][15][16][17][18][19] Correlation rates have been similarly high in studies that focused exclusively on head and neck cases, ranging from 96 to 98%. [10][11][12][13]15 However, there are few studies involving large academic centers.…”
mentioning
confidence: 99%
“…15,16 False positive reports have also been noted, resulting in wider resection margins which complicate surgical closure and subsequent functional outcomes. 17 As frozen-section examination was not encouraged by our histopathology department, a low threshold for second look procedures was adopted in our department as an acceptable practice. All patients in the current series were made aware of this possibility during the consent process.…”
mentioning
confidence: 99%